PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR DAN KEMAMPUAN BERTANYA SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS XI IPA SMA N 1 KUTALIMBARU - Nurhasanah Siohotang; Ely Djulia; Sentosa Gurusinga (Jurnal Pelita Pendidikan, 2017)
This research aim to know whether is a significant influence learning result and ability to ask student by using cooperative learning model numbered head together (NHT) in human respiratory system subject matter grade XI science senior high school 1 Kutalimbaru academic year 2016/2017. The population in this research is all students that consist of 3 classes totaling 116 students. The sample was taken in random sampling as many as 80 students. XI IPA 1 is an experimental class using cooperative learning model numbered head together (NHT) as many as 40 students, while XI IPA 3 as the control class using lecture and question and answer method as many as 40 students. Th method of this research is quasi-experimental. Based on the average value seen their influence learning result and the ability to ask student by using cooperative learning model numbered head together (NHT) which indicate that the value posttest students in the experimental class is 82.9 and SD 6.3. While the average value in the control class is 79.25 with SD of 5.86. The influence of learning result is also proven through hypothesis testing by using t test with the level of trust α = 0,05, where t count> t tab (6,66> 2,001), which means in this research Ho rejected and Ha accepted. The average score of student ability ask in the experimental class is 60,5% belongs to good predicate and control class is 32,5% belongs to bad predicate. It can be concluded that there is significant influence using cooperative learning model numbered head together (NHT) for learning result and the ability to ask student in human respiratory system subject matter in grade XI science senior high school 1 Kutalimbaru T.P. 2016/2017.Keywords: Learning result, Cooperative Learning Type Numbered Head Together, Human Respiratory System.